Modeling and optimization of a hybrid system for the energy supply of a “Green” building - Dagdougui, Hanane; Minciardi, Riccardo; Ouammi, Ahmed; Robba, Michela; Sacile, Roberto (Energy conversion and management, 2012)
► The system model is embedded in a dynamic decision model. ► The model has been applied to a specific case study. ► Optimal results are reported for two main cases: the presence/absence of the energy storage system. Renewable energy sources (RES) are an “indigenous” environmental option, economically competitive with conventional power generation where good wind and solar resources are available. Hybrid systems can help in improving the economic and environmental sustainability of renewable energy systems to fulfill the energy demand. The aim of this paper is to present a dynamic model able to integrate different RES and one storage device to feed a “Green” building for its thermal and electrical energy needs in a sustainable way. The system model is embedded in a dynamic decision model and is used to optimize a quite complex hybrid system connected to the grid which can exploit different renewable energy sources. A Model Predictive Control (MPC) is adopted to find the optimal solution. The optimization model has been applied to a case study where electric energy is also used to pump water for domestic use. Optimal results are reported for two main cases: the presence/absence of the energy storage system.